Training community health workers: an evaluation of effectiveness, sustainable continuity, and cultural humility in an educational program in rural Haiti. Issue 4 (4th July 2017) - Knettel, Brandon A.; Slifko, Shay E.; Inman, Arpana G.; Silova, Iveta
Abstract: Community health worker (CHW) programs, which provide health-related training to members of the general public, have emerged as a key tool in addressing the health needs of the world's poorest citizens. The Caribbean nation of Haiti is widely considered the least developed in the Western hemisphere with health indicators near the bottom of all countries worldwide. In response to the vast healthcare needs of the country, attempts have been made to extend sustainable rural health services with a small number of CHW programs formed through international and community partnerships. The purpose of the current mixed methods research was to evaluate the efficacy, sustainability, and cultural compatibility of an annual volunteer-led training program for CHWs in rural southeast Haiti. The course aimed to expand the health literacy of 126 Haitian CHWs with a specific focus on maternal and child health. Results showed significant improvement in participants' knowledge of course content and participants overwhelmingly endorsed the course as valuable. However, trainees cited logistical, material, and financial barriers impeding them from carrying out their roles as CHWs. Additionally, although the partnership responsible for the ongoing training is taking a long-term stance to their work in Haiti, training provided by non-Haitian, short-term volunteers creates concerns about a lack of sustainable continuity and cultural compatibility. In response, the authors provide recommendations for building effective, volunteer-led training programs that uphold principles of participatory action and cultural humility.